2014
DOI: 10.1177/1352458514551453
|View full text |Cite
|
Sign up to set email alerts
|

Puberty in females enhances the risk of an outcome of multiple sclerosis in children and the development of central nervous system autoimmunity in mice

Abstract: Puberty in females enhances CNS autoimmune mechanisms that lead to MS in humans and EAE in mice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
51
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(52 citation statements)
references
References 36 publications
1
51
0
Order By: Relevance
“…Prior studies have suggested that attainment of menarche increases the risk of MS in girls with acute demyelinating syndrome (ADS),4 and that relapse rate increases in girls in the peri‐menarcheal phase 5. One study has demonstrated a marginally earlier age at menarche in a large cohort of females with MS 2.…”
Section: Introductionmentioning
confidence: 99%
“…Prior studies have suggested that attainment of menarche increases the risk of MS in girls with acute demyelinating syndrome (ADS),4 and that relapse rate increases in girls in the peri‐menarcheal phase 5. One study has demonstrated a marginally earlier age at menarche in a large cohort of females with MS 2.…”
Section: Introductionmentioning
confidence: 99%
“…Consistent with 2 recent reports of smaller cohorts, the observed temporal link between onset of menarche and MS in our sample supports the potential role of sex hormones in the complex immunologic process occurring in the onset of MS in adolescent girls. 28,29 Clinical features that distinguished younger versus older MS cases included the following: younger children were more likely to report a prodromal event before the first MS attack, present with encephalopathy, and have more motor and coordination problems. In contrast, older children had more sensory symptoms suggesting spinal cord involvement (similar to findings recently reported from Germany comparing 47 children aged <11 years with those >14 years of age, 30 and more consistent with findings reported for adult-onset MS).…”
Section: Treatmentmentioning
confidence: 99%
“…12 In a prospective longitudinal study of Canadian children presenting for an acquired demyelinating syndrome (ADS), girls with later age at menses were less likely to be diagnosed with MS even after correcting for older age at ADS onset. 13 In a US cohort of female pediatric patients with MS followed before, during, and after menarche, individual relapse rates were higher during the epoch of menarche (defined as 6 months before and after menarche) compared to relapse rates postmenarche. 14 Younger girls (at least 6 months prior to menarche) had a lower relapse rate compared to girls within 6 months of menarche in unadjusted models; however, there was no difference after adjusting for exposure to disease-modifying therapy.…”
mentioning
confidence: 99%